Relations between risk perception, perceptions of peers’ driving, and risky driving among Cambodian adolescents - Lim, Bouyheak; Lahar, Cindy J.; Dang, Hoang-Minh; Weiss, Bahr (Frontiers in Psychology, 2023)
Traffic accidents are a leading cause of death globally, with substantial economic impact particularly in low-and-middle-income countries (LMIC). Adolescents are at particular risk, partly due to their tendency to engage in risky driving. However, most research designed to identify potential causes of risky adolescent driving has been conducted in Western, high-income countries, which often have substantial cultural differences from LMIC that potentially influence risky adolescent driving. The present study, one of the first focused on this topic in Southeast Asia, cross-sectionally assessed 425 adolescent motorbike drivers in the Southeast Asian LMIC Cambodia. Adolescents’ (a) beliefs about peers’ driving (social norms) and (b) driving risk perception were assessed as predictors of four risky driving behaviors: aggressive driving; distracted driving; intoxicated driving; violating driving laws. Canonical correlation analysis identified a general relation between (a) beliefs about peers’ driving, and (b) all four risky driving behaviors, with R2=.35 indicating over one-third of the variance in risky driving was explained by perceptions of peers’ driving. Risk perception was not involved in the significant canonical relation, however. Gender moderated two of the underlying relations, with females showing larger relations between perceptions of friends’ driving, and distracted driving and violating driving laws. These findings provide useful directions for future research (e.g., assessing the accuracy of Cambodian adolescents’ perceptions of peers’ driving) useful for helping stakeholders tailor road safety programs (e.g., providing adolescent drivers with accurate information regarding their peers’ actual driving behaviors) for adolescent motorcyclists in Cambodia and similar countries.